An in vivo Biomarker to Characterize Ototoxic Compounds and Novel Protective Therapeutics - Bellairs, Joseph A.; Redila, Van A.; Wu, Patricia; Tong, Ling; Webster, Alyssa; Simon, Julian A.; Rubel, Edwin W.; Raible, David W. (Frontiers in Molecular Neuroscience, 2022)
There are no approved therapeutics for the prevention of hearing loss and vestibular dysfunction from drugs like aminoglycoside antibiotics. While the mechanisms underlying aminoglycoside ototoxicity remain unresolved, there is considerable evidence that aminoglycosides enter inner ear mechanosensory hair cells through the mechanoelectrical transduction (MET) channel. Inhibition of MET-dependent uptake with small molecules or modified aminoglycosides is a promising otoprotective strategy. To better characterize mammalian ototoxicity and aid in the translation of emerging therapeutics, a biomarker is needed. In the present study we propose that neonatal mice systemically injected with the aminoglycosides G418 conjugated to Texas Red (G418-TR) can be used as a histologic biomarker to characterize in vivo aminoglycoside toxicity. We demonstrate that postnatal day 5 mice, like older mice with functional hearing, show uptake and retention of G418-TR in cochlear hair cells following systemic injection. When we compare G418-TR uptake in other tissues, we find that kidney proximal tubule cells show similar retention. Using ORC-13661, an investigational hearing protection drug, we demonstrate in vivo inhibition of aminoglycoside uptake in mammalian hair cells. This work establishes how systemically administered fluorescently labeled ototoxins in the neonatal mouse can reveal important details about ototoxic drugs and protective therapeutics.